The Functional Head Impulse Test to Assess Oscillopsia in Bilateral Vestibulopathy - van Dooren, T. S.; Lucieer, F. M. P.; Duijn, S.; Janssen, A. M. L.; Guinand, N.; Pérez Fornos, A.; Van Rompaey, V.; Kingma, H.; Ramat, S.; van de Berg, R. (Frontiers in Neurology, 2019)
Introduction. Bilateral vestibulopathy (BV) is a chronic condition in which vestibular function is severely impaired or absent on both ears. Oscillopsia is one of the main symptoms of BV. Oscillopsia can be quantified objectively by functional vestibular tests, and subjectively by questionnaires. Recently, a new technique for visual stabilization abilities was developed: the functional head impulse test (fHIT). This study compared the fHIT with the Dynamic Visual Acuity assessed on a treadmill (DVAtreadmill) and Oscillopsia Severity Questionnaire (OSQ) in the context of objectifying dynamic visual acuity and the experience of oscillopsia in patients with BV. Methods. Inclusion criteria comprised: 1) summated slow phase velocity of nystagmus of <20°/s during bithermal caloric tests, 2) torsion swing tests gain of <30% and/or phase <168°, and 3) complaints of oscillopsia and/or imbalance. During the fHIT (BEON Solutions srl, Italy) patients were seated in front of a computer screen. During a passive horizontal head impulse a Landolt C optotype was shortly displayed. Patients reported the seen optotype by pressing the corresponding button on a keyboard. The percentage correct answers was registered for leftwards and rightwards head impulses separately. During DVAtreadmill patients were positioned on a treadmill in front of a computer screen that showed Sloan optotypes. Patients were tested in static condition and in dynamic conditions (while walking on the treadmill at 2, 4, and 6km/h). The decline in LogMAR between static and dynamic conditions was registered for each speed. Every patient completed the Oscillopsia Severity Questionnaire (OSQ). Results. In total 23 patients were included. This study showed a moderate correlation between OSQ outcomes and the fHIT (rightwards head rotations (rs = -0.559; p= 0.006) leftwards head rotations (rs =-0.396; p = 0.061)). No correlation was found between OSQ outcomes and DVAtreadmill, or between DVAtreadmill and fHIT. All patients completed the fHIT, 52% of the patients completed the DVAtreadmill on all speeds. Conclusion. The fHIT seems to be a feasible test to quantify oscillopsia in BV since, unlike DVAtreadmill, it correlates with the experienced oscillopsia measured by the OSQ, and more BV patients are able to complete the fHIT than DVAtreadmill.